2017
DOI: 10.5194/acp-17-3929-2017
|View full text |Cite
|
Sign up to set email alerts
|

A quantification method for heat-decomposable methylglyoxal oligomers and its application on 1,3,5-trimethylbenzene SOA

Abstract: Abstract. Methylglyoxal forms oligomeric compounds in the atmospheric aqueous particle phase, which could establish a significant contribution to the formation of aqueous secondary organic aerosol (aqSOA). Thus far, no suitable method for the quantification of methylglyoxal oligomers is available despite the great effort spent for structure elucidation. In the present study a simplified method was developed to quantify heat-decomposable methylglyoxal oligomers as a sum parameter. The method is based on the the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 118 publications
1
7
2
Order By: Relevance
“…However, in triphasic experiments performed at high RH for 7–8 h SOA composition is characterized by a wide variety of different and longer oligomers compared to experiments started in dry conditions. On the one hand, this is in contrast to what was observed in previous studies by Zhang et al 45 and by Nguyen et al 15 On the other hand, Rodigast et al 46 observed a dependence of oligomer formation from methylglyoxal not only on RH but also on pH of seed particles, which may partly explain our results, as methylglyoxal is one of the reaction products.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in triphasic experiments performed at high RH for 7–8 h SOA composition is characterized by a wide variety of different and longer oligomers compared to experiments started in dry conditions. On the one hand, this is in contrast to what was observed in previous studies by Zhang et al 45 and by Nguyen et al 15 On the other hand, Rodigast et al 46 observed a dependence of oligomer formation from methylglyoxal not only on RH but also on pH of seed particles, which may partly explain our results, as methylglyoxal is one of the reaction products.…”
Section: Discussioncontrasting
confidence: 99%
“… 42 44 Concerning isoprene SOA, Zhang et al 45 and Nguyen et al 15 established that a high relative humidity (RH) suppresses oligomer formation not only in the case of condensation reactions (accompanied by loss of a water molecule) but also for hemiacetal formation. Conversely, Rodigast et al 46 highlighted a contradicting dependence of oligomer formation from methylglyoxal (an isoprene oxidation product) under varying RH and pH. Oligomerization from isoprene oxidation can occur also from acid-catalyzed ring-opening reactions of multifunctional epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of NO x gave nitrogen-containing C 9 compounds with one or two N atoms and C 18 compounds with only one N atom, in addition to HOM monomers and HOM dimers. These compounds are expected to be nitrates or peroxy nitrates, as it is highly unlikely to form nitro-aromatic compounds from TMB (Sato et al, 2012). N-containing compounds were the dominating species in experiments with NO x (see Fig.…”
Section: Influence Of No Xmentioning
confidence: 99%
“…However, these studies indicate that AVOCs have a strong potential to form HOMs under NO x -free conditions and proposed that they may play a crucial role in NPF and particle growth of SOA in urban areas. Regarding SOA yields, a number of smog chamber studies have been conducted in order to investigate the oxidation of TMB with OH radicals under different NO x and aerosol seed conditions (Paulsen et al, 2005;Rodigast et al, 2017;Wyche et al, 2009;Huang et al, 2015;Sato et al, 2012). They reported that under higher NO x : VOC conditions, SOA yield is reduced compared to medium or lower NO x : VOC conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies indicate that AVOCs have a strong potential to form HOM under NOx free conditions and proposed that they may play a crucial role in NPF and particle growth of SOA in urban areas. Regarding SOA yields a number of smog chamber studies have been conducted in order to investigate the oxidation of TMB with OH radical under different NOx and aerosol seed conditions (Paulsen et al, 2005;Rodigast et al, 2017;Wyche et al, 2009;Sato et al, 2018;Huang et al, 2015). They reported that under higher NOx:VOC conditions, SOA yield is reduced compared to medium or lower NOx:VOC conditions.…”
mentioning
confidence: 99%